2015
DOI: 10.1016/j.biochi.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The M1 family of vertebrate aminopeptidases: Role of evolutionarily conserved tyrosines in the enzymatic mechanism of aminopeptidase B

Abstract: Aminopeptidase B (Ap-B), a member of the M1 family of Zn(2+)-aminopeptidases, removes basic residues at the NH2-terminus of peptides and is involved in the in vivo proteolytic processing of miniglucagon and cholecystokinin-8. M1 enzymes hydrolyze numerous different peptides and are implicated in many physiological functions. As these enzymes have similar catalytic mechanisms, their respective substrate specificity and/or catalytic efficiency must be based on subtle structural differences at or near the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…We also observed that the tyrosine residue involved in the catalytic mechanism and generally located 80–90 residues after the HEXXHX 18 E motif in M1 aminopeptidases was conserved in Tma108 ( 40 ). The (G/A/H/V)(G/A)MEN motif, found in 77% of the M1 family proteins and involved in substrate binding and recognition ( 41 ), was also present in Tma108. Only the 293 M in the first position of the motif (MAMEN) is not congruent with the defined signature.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that the tyrosine residue involved in the catalytic mechanism and generally located 80–90 residues after the HEXXHX 18 E motif in M1 aminopeptidases was conserved in Tma108 ( 40 ). The (G/A/H/V)(G/A)MEN motif, found in 77% of the M1 family proteins and involved in substrate binding and recognition ( 41 ), was also present in Tma108. Only the 293 M in the first position of the motif (MAMEN) is not congruent with the defined signature.…”
Section: Resultsmentioning
confidence: 99%
“…In an “open” form of the protein, this residue undergoes a 6 Å shift away from the zinc ion, whereas in a closed form, this Tyr residue is proposed to both assist in the activation of the peptide bond and in the stabilization of the tetrahedral intermediate during the proteolytic catalytic cycle [ 21 , 22 ]. It has been shown, by site directed mutagenesis, that mutation of this Tyr residue into Phe completely abolished the enzyme activity [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ap-B, similar hydrogen bonds should not be established, owing to a Phe residue in position 297 instead of a tyrosine (Fig. 1-B, [26]). Thus, trans-resveratrol could interact differently with the Ap-B structure, which could explain why resveratrol has no significant effect on its activity.…”
Section: Determination Of Kinetic Parameters Of Ap-b With Arg-amc Submentioning
confidence: 96%